Systems modeling and computer simulation - Kheir, Naim A. (Marcel Dekker, 1996)
This second edition describes the fundamentals of modelling and simulation of continuous-time, discrete time, discrete-event and large-scale systems. Coverage new to this edition includes: a chapter on non-linear systems analysis and modelling, complementing the treatment of of continuous-time and discrete-time systems; and a chapter on the computer animation and visualization of dynamical systems motion.